2012
DOI: 10.1186/1472-6750-12-87
|View full text |Cite
|
Sign up to set email alerts
|

A novel strategy for efficient production of anti-V3 human scFvs against HIV-1 clade C

Abstract: BackgroundProduction of human monoclonal antibodies that exhibit broadly neutralizing activity is needed for preventing HIV-1 infection, however only a few such antibodies have been generated till date. Isolation of antibodies by the hybridoma technology is a cumbersome process with fewer yields. Further, the loss of unstable or slowly growing clones which may have unique binding specificities often occurs during cloning and propagation and the strongly positive clones are often lost. This has been avoided by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…In order to determine the diversity of the library we randomly picked 57 clones from the unselected library. Amplification of these scFvs was done by PCR, followed by digestion with BstN142. DNA fingerprinting revealed that 45/57 (79%) clones were unique (Figure S3).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In order to determine the diversity of the library we randomly picked 57 clones from the unselected library. Amplification of these scFvs was done by PCR, followed by digestion with BstN142. DNA fingerprinting revealed that 45/57 (79%) clones were unique (Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…Earlier, we used a combined approach of EBV immortalization of V3 specific B cells selected from a single HIV-1 infected donor, followed by construction of antigen preselected human anti-V3 recombinant scFv library of limited diversity; the advantage of such antigen (V3) preselected library being the ease of isolating V3 directed scFv monoclonals42.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations